PENINGKATAN KOMPETENSI MELAKUKAN RAPAT PADA PESERTA DIDIK OTOMATISASI TATA KELOLA PERKANTORAN MELALUI IMPLEMENTASI PEMBELAJARAN INTEGRATED - Kusumaningrum, Kusumaningrum (JISPE Journal of Islamic Primary Education, 2021)
This study aims to improve the competence of conducting meetings for class XI students of the Office Administration Automation Expertise Program at SMK Negeri 3 Surakarta in the 2019/2020 academic year through the application of integrated learning assisted by video tutorial based learning. This research is a classroom action research. As a teaching teacher as well as a researcher who will carry out teaching by applying the Integrated video tutorial learning model that has been planned. Based on the data analysis of the research results in the first cycle, there were 24 students who paid attention and the second cycle became 32 students who paid attention or were included in the very good category. Furthermore, in the conducive aspect of the implementation of group discussions, there was an increase to 30 students who paid attention and concentration or 93.75% included in the very good category of cycle I where there were only 24 students who paid attention and concentration or 71.87%. In the aspect of the intensity of the implementation of group discussions after listening to the broadcast, there were 22 students who paid attention or 68.75% and were included in the sufficient category in the first cycle, in the second cycle there were 32 students or 100% and included in the very good category. In the last aspect, namely the reflectivity of reflection activities at the end of the lesson so that students know the shortcomings and what will be done next, there are 29 students or 90.62% categorized as very good and has increased from cycle I.